Upaya Meningkatkan Motivasi dan Hasil Belajar Menggunakan Metode Diskusi Materi Tema 3 Sub Tema Penemu Yang Mengubah Dunia pada Siswa Kelas VI MI Darul Muta’allimin Dayu Purwoasri Kediri - Marsiani, Marsiani (Universitas Nusantara PGRI Kediri, 2022)
In learning the concepts of learning material carried out by researchers in class, the existing reality shows that students' motivation to learn and learning activities are still felt to be less exciting. To increase students' understanding of the material presented, the teacher must be active in providing variations in learning, so that students do not become bored so that blocking of the material occurs. Students should have space to convey their thoughts so that boredom does not occur at every meeting in learning. The most appropriate method is discussion because here students are taught how to think critically. There is at least two-way communication when applying the discussion method. According to Gulo (2002) he argued that the discussion method is an appropriate learning method to improve the quality of interaction between students. The goal is to gain a clearer and more thorough shared understanding of something, as well as to prepare and finalize joint decisions. From the results of the analysis that the discussion method can increase student motivation. This can be shown from observations in the learning process cycle 1 getting 2.56 with the sufficient category, and in cycle 2 getting 3.5 with the category belonging to good. The discussion method can improve student learning outcomes. This can be shown from the increase in classical completeness, the number of students who meet KKM standards and the class average score. In cycle 1, it was found that there were 22 students who completed with classical completeness of 75.86% and an average grade of 73.86. In cycle 2, it was found that there were 25 students who completed with classical completeness of 86.21% with an average grade of 81.34. So it can be concluded that the discussion method can increase the motivation and learning outcomes of Class VI students MI Darul Muta'allimin Dayu Purwoasri Kediri Odd Semester 2021/2022 Academic Year in Material Theme 3 Sub Themes Inventors Who Changed the World.